(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, continuity, consistency, improvement of natural scientific literacy in the field of pedagogical education for general secondary educational institutions, organization and management of the educational process at a high level, open information and education in improving the efficiency of the qualifications of biology teachers information on creating an environment and improving usage indicators is covered.